Outstanding Marine Molecules 2014
DOI: 10.1002/9783527681501.ch05
|View full text |Cite
|
Sign up to set email alerts
|

Glycolipids from Marine Invertebrates

Abstract: Glycolipids constitute a broad class of natural compounds belonging to the glycoconjugates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 213 publications
0
4
0
Order By: Relevance
“…In the field of natural product chemistry, the marine environment has proven to be a rich source of structurally diverse and biologically active compounds including glycolipids. In 2011, Wojnar and Northcote described the isolation of agminosides A–E (Figure ), a group of structurally related, complex, and unusual glycolipids, from the marine sponge Raspailia agminata. , Sponge specimens of R. agminata were collected by hand from Taheke Reef in the Cavalli Islands, New Zealand.…”
Section: Introductionmentioning
confidence: 99%
“…In the field of natural product chemistry, the marine environment has proven to be a rich source of structurally diverse and biologically active compounds including glycolipids. In 2011, Wojnar and Northcote described the isolation of agminosides A–E (Figure ), a group of structurally related, complex, and unusual glycolipids, from the marine sponge Raspailia agminata. , Sponge specimens of R. agminata were collected by hand from Taheke Reef in the Cavalli Islands, New Zealand.…”
Section: Introductionmentioning
confidence: 99%
“…Given the biological relevance and structural complexity of these classes of compounds, a large number of reviews [ 6 , 7 , 8 , 9 , 10 , 11 , 12 ], books, and book chapters [ 13 , 14 , 15 ] have been devoted to all aspects related to their chemistry and biology. More specifically, in the field of glycolipids of marine origin, several excellent reviews have been published, especially by Barnathan et al [ 16 ], which represents an excellent description of all the glycolipids found in marine invertebrates, as well as by Li et al [ 17 ], which focused on the chemistry and biology of glycoglycerolipids from marine organisms. In addition, numerous reviews have been reported on very specific compounds, such as KRN7000 [ 18 ] and related glycosphingolipids [ 19 ] due to their outstanding biological activities and their potential pharmacological activity.…”
Section: Introductionmentioning
confidence: 99%
“…Glycolipids belong to the broad class of glycoconjugates and are characterized by having one or more monosaccharide residues linked by a glycosidic bond to a hydrophobic moiety, such as an acylglycerol, a sphingoid, or a prenyl phosphate [1]. Glycolipids, including glycosphingolipids and gangliosides, are widely found in marine invertebrates, especially in echinoderms (sea stars, sea cucumbers) and sponges, and show a large variety of biological activities such as antitumor, immunomodulatory and nitric oxide release-inhibiting activities [2]. …”
Section: Introductionmentioning
confidence: 99%